Effect of Social Media Overload on Employees’ Job Performance in Nepalese Banking Sector - Sah, Bandana Kumari (Nepalese Journal of Business, 2025)
This study examines the effect of social media overload on employees’ job performance in Nepalese banking sector. Employees’ job performance is the dependent variable. The selected independent variables are poor communication, time management, shared vision, social interaction and work-life balance. The study is based on the primary data with 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and effect of social media overload on employees’ job performance in Nepalese banking sector. The study showed a negative impact of poor communication on employees’ job performance. It indicates that poor communication provided by banks leads to decrease the employees’ job performance in banking sector. Likewise, time management is positively correlated to employees’ performance. It indicates that effective time management leads to increase the performance of employees in banks. Similarly, shared vision is positively correlated to employees’ job performance. It indicates that to increase the employees’ performance goals and vision be shared. Further, social interaction is also positively correlated to the employees’ job performance. It indicates that regular team-building activities leads to increase the employees’ job performance. Moreover, work-life balance is positively correlated to the employees’ job performance. It indicates that flexibility in work hours leads to increase the employees’ job performance.